2021
DOI: 10.2807/1560-7917.es.2021.26.12.2100329
|View full text |Cite
|
Sign up to set email alerts
|

Robust antibody responses in 70–80-year-olds 3 weeks after the first or second doses of Pfizer/BioNTech COVID-19 vaccine, United Kingdom, January to February 2021

Abstract: Sera were collected from 185 adults aged ≥ 70 years in London to evaluate the immune response to COVID-19 vaccines. A single dose of Pfizer/BioNtech vaccine resulted in > 94% seropositivity after 3 weeks in naïve individuals using the Roche Spike antibody assay, while two doses produced very high spike antibody levels, significantly higher than convalescent sera from mild-to-moderate PCR-confirmed adult cases. Our findings support the United Kingdom’s approach of prioritising the first dose and delaying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 5 publications
(4 reference statements)
3
36
0
1
Order By: Relevance
“…Although the evidence on single-dose immunogenicity of BNT162b2 in older adults is mixed, [28][29][30] pooled data from four ChAdOx1 trials, including over 950 participants aged 70 years and older, indicated vaccine effectiveness of 63•9% (95% CI 46-75•9) against all infection at 22-90 days after a single dose, 17 which is in line with our findings. Our estimates of vaccine effectiveness against all infection are not dissimilar to those from phase 3 efficacy testing of the single-dose Ad26.COV2.S vaccine (Janssen), which was 67•9% (95% CI 38•2-82•8) effective against symptomatic COVID-19 at 28 days or more after vaccination in those aged 60 years and older.…”
Section: Chadox1 Bnt162b2supporting
confidence: 88%
“…Although the evidence on single-dose immunogenicity of BNT162b2 in older adults is mixed, [28][29][30] pooled data from four ChAdOx1 trials, including over 950 participants aged 70 years and older, indicated vaccine effectiveness of 63•9% (95% CI 46-75•9) against all infection at 22-90 days after a single dose, 17 which is in line with our findings. Our estimates of vaccine effectiveness against all infection are not dissimilar to those from phase 3 efficacy testing of the single-dose Ad26.COV2.S vaccine (Janssen), which was 67•9% (95% CI 38•2-82•8) effective against symptomatic COVID-19 at 28 days or more after vaccination in those aged 60 years and older.…”
Section: Chadox1 Bnt162b2supporting
confidence: 88%
“…Overall, older men had a nearly 50% lower anti-SARS-CoV-2 RBD total antibody response compared to young women [11]. Similar evidence was garnered in other studies, whereby lower vaccine immunogenicity was also reported in older people and/or in males [17][18][19][20][21]. Given the increased risk for poor COVID-19 progression and outcomes associated with advanced age and male sex, these groups may be especially vulnerable in the setting of a diminished immune response [22].…”
Section: Why?supporting
confidence: 63%
“…Outside trials, there are limited data on post-vaccine antibody responses in other groups, especially older adults who were underrepresented in the ChAdOx1 trial 5 . A study of 185 individuals aged >70 years showed high seropositivity after one or two BNT162b2 doses 10 . Another study, of 100 individuals aged 80–100 years, showed almost universal high antibody responses 3 weeks after a single dose of BNT162b2, with spike-specific cellular responses in 63% of participants 11 .…”
Section: Mainmentioning
confidence: 99%